EFEKTIVITAS EKSTRAK SEREH WANGI (Cymbopogon nardus L. Rendle) TERHADAP KECOAK JERMAN (Blattella germanica L.) Populasi VCRU-WHO, GFA-JKT DAN HHB-JKT - Sahara, Syafni - (STKIP PGRI Sumbar, 2014)
German cockroaches are one of insect species that pests classified, because it is habit whichdamaging the cloth, books and other household equepments. In addition, cockroaches also left the smallof area or in a food which visited. Cockroach act as a vector of diseases such as diarrhea, dysentery,cholera, typhoid, and leprosy, as well as can cause asthma and allergies of human. Long standingcockroach controled by use of synthetic insecticiedes. The use of synthetic insecticides in not only has theadventages but also has disadvantages. Furthermore, necessary to find other alternative are safe for theenviroment. The one of is use of plant base insecticides such as extracts of sereh wangi (Cymbopogonnardus). This research aims to determine the potensial of sereh wangi in controlling the population ofmale german cockroach VCRU-WHO, GFA-JKT, and HHB-JKT. This research used an experimentalmethode with glass jar (kontak) using a three population of german cockroach. The experimentalcockroach was use an adult male cockroach which was about 2 until 3 months and everytime treathmentis done three time replay. Based on the on the criteria of effectiveness of insecticide that prepared by thedirectorate of fertilizer and pesticides (2004) the consentration of sereh wangi extract has not beeneffectively use to immobilize and lethal german cockroach population VCRU-WHO, GFA-JKT, andHHB-JKT because KT90> 20 minutes and LT90> 6 hours.